Engineered Accumulation of Bicarbonate in Plant Chloroplasts: Known Knowns and Known Unknowns - Rottet, Sarah; Förster, Britta; Hee, Wei Yih; Rourke, Loraine M.; Price, G. Dean; Long, Benedict M. (Frontiers in Plant Science, 2021)
Heterologous synthesis of a biophysical CO2-concentrating mechanism (CCM) in plant chloroplasts offers significant potential to improve the photosynthetic efficiency of C3 plants and could translate into substantial increases in crop yield. In organisms utilizing a biophysical CCM, this mechanism efficiently surrounds a high turnover rate Rubisco with elevated CO2 concentrations to maximize carboxylation rates. A critical feature of both native biophysical CCMs and one engineered into a C3 plant chloroplast is functional bicarbonate (HCO3−) transporters and vectorial CO2-to-HCO3− converters. Engineering strategies aim to locate these transporters and conversion systems to the C3 chloroplast, enabling elevation of HCO3− concentrations within the chloroplast stroma. Several CCM components have been identified in proteobacteria, cyanobacteria, and microalgae as likely candidates for this approach, yet their successful functional expression in C3 plant chloroplasts remains elusive. Here, we discuss the challenges in expressing and regulating functional HCO3− transporter, and CO2-to-HCO3− converter candidates in chloroplast membranes as an essential step in engineering a biophysical CCM within plant chloroplasts. We highlight the broad technical and physiological concerns which must be considered in proposed engineering strategies, and present our current status of both knowledge and knowledge-gaps which will affect successful engineering outcomes.